Effect of serum calcium status at calving on survival, health, and performance of postpartum Holstein cows and calves under certified organic management - Wilhelm, A.L.; Maquivar, M.G.; Bas, S.; Brick, T.A.; Weiss, W.P.; Bothe, H.; Velez, J.S.; Schuenemann, G.M. (Journal of dairy science, 2017)
The study objective was to assess the effect of hypocalcemia (HYPO; ≤2.0 mmol/L) of the dam at calving on survival, health, and performance of lactating dairy cows and their calves under certified organic management. Prepartum dairy cows (primiparous, n = 445; multiparous, n = 328) from 1 dairy herd were monitored (prepartum pen) for imminent signs of parturition (appearance of amniotic sac outside the vulva) until birth. All calves were subject to the same newborn care, colostrum management, and failure of passive transfer assessment (serum total protein ≤5.5 mg/dL). Serum total calcium of cows was determined in samples taken within 2 h after calving. To define HYPO cows after calving, a cut-point of total serum Ca concentration with optimal sensitivity and specificity to predict metritis or calf diarrhea was established by using the receiver operator characteristic. The effect of HYPO on survival (died or culled within 60 DIM), health status, and pregnancy per artificial insemination (PAI) for first services of lactating cows were analyzed using the GLIMMIX procedure of SAS. Additionally, the effect of HYPO at calving on days in milk (DIM) at first service (DIMFS), milk yield (kg), milk components (percent fat and protein), and somatic cell count were analyzed for the first 3 Dairy Herd Improvement Association (DHIA) tests using the MIXED procedure of SAS (SAS Institute Inc., Cary, NC). The effect of parity (primiparous and multiparous), body condition score at calving, and manure hygiene score at calving were also included in the statistical models. The effect of HYPO at calving on calf survival, serum total protein, and diarrhea within 10 d of age were assessed using GLIMMIX procedure of SAS. The overall prevalence of HYPO was 14.6% (2.7% for primiparous and 30.8% for multiparous cows). Cows experiencing HYPO at calving had greater proportion of metritis (25.1 vs. 14.7%) and culling within 60 DIM (15.9 vs. 6.8%) compared with non-HYPO cows, respectively. For the first 3 DHIA tests, milk yield and components did not differ between HYPO and non-HYPO cows. The DIMFS as well as proportion of cows with dystocia, births of twins, mastitis, and PAI at first service were not different between HYPO and non-HYPO cows. The proportion of stillbirth, weaned calves, and serum total protein did not differ between calves born from HYPO or non-HYPO cows. However, calves born from HYPO cows had greater incidence of diarrhea (49%) than calves born (33.3%) from non-HYPO cows. Findings from the present study showed that HYPO at calving had significant health implications for both dams and calves under certified organic management.